PENGARUH KEPEMIMPINAN, MOTIVASI DAN PARTISIPASI ANGGOTA TERHADAP MANAJEMEN KINERJA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BMT ARTHA SALAM DI BANJARNEGARA - Lustono Lustono; Asih Muqoronah (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2021)
ABSTRACT The problem that occurs in KSPPS BMT Artha Salam Sigaluh branch Of Sigaluh is that performance management has not been carried out optimally as indicated by leadership, motivation and member participation. Cooperative performance management has not been carried out optimally or effectively as expected due to the lack of leadership, motivation and member participation. This researcher aims to determine the effect of leadership, motivation and member participation partially and simultaneously on performance management, as well as more dominant variables. This research is a quantitative research. The data used in this study are primary data with questionnaires. The population in this study were employees of the cooperative member who receive the remaining results of business (SHU) KSPPS BMT Artha Salam Branch Sigaluh. The sampling technique in this study is to use all member of the cooperative who receive the ramainder of the business (SHU), amounting to 64 respondents. Data analysis in this study uses multiple linear regression analysis. Based on the results of the hypothesis test there is a simultaneous influence between the variables of leadership, motivation and member participation to performance management. Partially shows no significant effect between the leadership variables on performance management variables. The variable motivation influance to performance management. While the member participation variable influences performance management. The variable that has dominant influence on performance management is member participation.